Estudo comparado sobre a flexibilidade comportamental das castas de duas espécies de vespas eussociais do gênero Mischocyttarus (Hymenoptera, Vespidae, Mischocyttarini) - Costa Filho, Vanderlei Conceição [UNESP] (2014)
Wasps of the genus Mischocyttarus being relatively abundant and easy to handle and observe, provide a great material for the study of social behavior of castes. Two species of Mischocyttarus, M. cerberus styx and M. cassununga, were observed under natural field conditions. During the observations, experimental manipulations were carried out to test how it would react to the removal of some individuals to different categories and social ranking over a six-day. The results showed a significant difference on the number of forage activities when removing individuals from the intermediate category of M. cerberus styx, i.e., those that exhibit behavioral characteristics of dominant and foragers. Moreover, no significant differences on the number of forage activities to any of the manipulations performed on M. cassununga were observed. Thus, M. cerberus styx was more susceptible to break the social hierarchy and have high behavioral flexibility. M. cassununga already shown to have a stronger hierarchy, being less susceptible to external changes, and despite also having behavioral flexibility, it takes more time process than in other species